THERMODYNAMIC PROPERTIES OF PROPANE HYDRATE IN THE NEIGHBORHOOD OF THE HYDRATE-ICE AND HYDRATE-WATER PHASE TRANSITION POINTS - Buleyko V.M.; Makogon Yu.F. (My University, 1989)
Interest in the thermodynamic properties of gas hydrates is on the rise. A thorough knowledge of these properties would provide a basis for the effective use of these hydrates in various technologies, for finding new methods of preventing hydrate formation in systems for the extraction, transport, processing and use of hydrocarbons, and for effective gas-hydrate prospecting, exploration and extraction both on land and in the oceans. Knowledge of the thermal properties of gas hydrates should result in the most accurate phase diagrams for the liquefied gas-water system in pressure, temperature and composition coordinates. The hydrate-ice and hydrate-water phase transitions are spread out over 2 to 3 degrees, which makes it impossible to distinguish between the heat associated with the hydrate-ice and hydrate-water transitions in the temperature interval between 270 and 273.16 K. Thus, in the range encompassing 0°C, the correct procedure is to measure the heat of the hydrate-water phase transition. The use of adiabatic calorimetry to investigate gas hydrates considerably increases the accuracy of the measurements and provides important data for theoretical and practical uses.